Using affective and behavioural sensors to explore aspects of collaborative music making. Issue 82 (October 2015) - Morgan, Evan; Gunes, Hatice; Bryan-Kinns, Nick
Abstract: Our research considers the role that new technologies could play in supporting emotional and non-verbal interactions between musicians during co-present music making. To gain a better understanding of the underlying affective and communicative processes that occur during such interactions, we carried out an exploratory study where we collected self-report and continuous behavioural and physiological measures from pairs of improvising drummers. Our analyses revealed interesting relationships between creative decisions and changes in heart rate. Self-reported measures of creativity, engagement, and energy were correlated with body motion; whilst EEG beta-band activity was correlated with self-reported positivity and leadership. Regarding co-visibility, lack of visual contact between musicians had a negative influence on self reported creativity. The number of glances between musicians was positively correlated with rhythmic synchrony, and the average length of glances was correlated with self-reported boredom. Our results indicate that ECG, motion, and glance measurements could be particularly suitable for the investigation of collaborative music making. Abstract : Highlights: We carry out experiments with pairs of co-present improvising drummers. We collect physiological and behavioural data, as well as self-report measures. Relationships are found between creative decisions and heart rate changes. We show that body motion and beta-activity relate to creativity and leadership. We show co-visibility impacts creativity; glances relate to synchrony and boredom.